FOSTERING STUDENTS LOVE FOR THE QURAN THROUGH TAHFIDZUL QURAN ACTIVITIES AT SMP MUHAMMADIYAH AHMAD DAHLAN AEKKANOPAN - Safira Achmad Pane; Silvia Febrianti (Proceeding International Seminar of Islamic Studies, 2022)
Al-Quran is the holy book of Muslims which was revealed to the Prophet Muhammad SAW as a way of life for Muslims. Love for the Quran needs to be grown in every human being, especially Muslims, one of them is by reading the verses of the Quran and understanding and practicing the contents contained in the Quran. The formulation of the problem related to this research is to grow students' love for the Quran through tahfidz activities at Muhammadiyah Middle School Ahmad Dahlan Aekkanopan. Meanwhile, the purpose of this research is to analyze the success of tahfidz Quran activities in growing students' love for the Quran. In this article, the research method used is a qualitative descriptive method in the form of observations on 9th grade students of Muhammadiyah Middle School Ahmad Dahlan Aekkanopan. Based on the results of observations made, it can be concluded that tahfidz activities can foster students' love of the Quran, this can be seen from the seriousness of students in memorizing the verses of the Quran, students' attitudes that reflect the contents of the Quranic verses such as cover the genitals, speak good words, be friendly, respect others and keep the environment clean. Keywords: Al-Quran, Students, Tahfidz